THE EFFECT OF HOSPITAL SERVICE QUALITY, PATIENT TRUST AND LOYALTY FROM THE PERSPECTIVE OF SERVICE ENCOUNTER ON JKN PARTICIPANTS AT LANGSA REGIONAL HOSPITAL - Ayu Sahara; Mohd Heikal; Ikramuddin; Sapna Biby; Nurainun; Naufal Bachri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to test the effect of service quality on patient loyalty with service encounter and patient trust as intervening variables in JKN participant patients at Langsa Regional Hospital. The number of respondents in this study was 203 JKN participant patients at Langsa Regional Hospital. The data analysis method used was Structural Equation Modeling with AMOS Software. The results of this study found that service quality directly had a positive and significant effect on service encounter and patient trust, but did not have a significant effect on patient loyalty, while service encounter had a positive and significant effect on patient trust and patient loyalty, and patient trust had a positive and significant effect on patient loyalty. The results of the mediation test found that service encounter was able to partially mediate the effect of service quality on patient trust, but was unable to significantly mediate the effect of service quality on patient loyalty, while patient trust was able to fully mediate the effect of service encounter on patient loyalty, but was unable to significantly mediate the effect of service quality on patient loyalty.